Playing with the city: street art and videogames - Márquez, Israel; Tosca, Susana (Arte, Individuo y Sociedad, 2016)
In this paper we introduce and describe the phenomenon of videogame street art as a specific kind of street art. We consider its materiality and significance, and conceptualize it in the light of a double manifestation of play: the playful appropriation of the city by the artist and the fact that Street art encapsulates the act of playing videogames in a visual form. Digital play spills out of our computer screens and occupies the urban space with the explicit intention of involving spectators, who are invited to play in symbolic ways that actualize nostalgic memories of gaming and can be related to a more general “play turn” in our culture.